Prognostic role of stereotactic body radiation therapy for elderly patients with advanced and medically inoperable pancreatic cancer. (23rd August 2017) - Zhu, Xiaofei; Li, Fuqi; Ju, Xiaoping; Cao, Fei; Cao, Yangsen; Fang, Fang; Qing, Shuiwang; Shen, Yuxin; Jia, Zhen; Zhang, Huojun
Abstract: The role of stereotactic body radiation therapy for the elderly with advanced or medically inoperable pancreatic cancer was still debated. Therefore, we evaluated the value of stereotactic body radiation therapy and its association with survival of those patients. A total of 417 elderly patients were retrospectively reviewed from 2012 to 2015. Overall survival (OS), progression‐free survival (PFS), local recurrence‐free survival (LRFS), distant metastasis‐free survival (DMFS), and toxicities were analyzed. Prescription doses ranged from 30–46.8 Gy in 5–8 fractions. Median age was 73 years old. Median OS, PFS, LRFS, and DMFS were 10, 8, 10, and 9.5 months, respectively. One‐year OS, PFS, LRFS, and DMFS rate were 35.5%, 18.2%, 26.6%, and 27.1%, respectively. Tumor stage and tumor response at 6 months and CA19‐9 levels normalization at 3 months after treatment were independent predictors of OS, PFS, LRFS, and DMFS. Patients with early‐stage cancer, better tumor response, and normalization of CA19‐9 levels had significantly longer OS, PFS, LRFS, and DMFS. Patients with the prodrug of 5‐FU and radiotherapy had longer survival than those with gemcitabine‐based chemotherapy and radiotherapy. Patients who received BED10  ≥ 60 Gy achieved better tumor response compared with those who received BED10  < 60 Gy. Two patients had grade 4 intestinal strictures. No grade 3 or higher hematologic toxicities occurred. Stereotactic body radiation therapy is safe and effective for elderly patients with advanced or medically inoperable pancreatic cancer. Early efficacy could be predictive of prognosis. Higher doses may be associated with efficacy but need further investigation. Abstract : The study demonstrated the feasibility and safety of stereotactic body radiation therapy for elder with locally pancreatic cancer, with acceptable survival and mild toxicities. Besides, higher doses may be associated with better tumor response.